The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/jbm.a.36397
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo evaluation of novel biodegradable Mg‐Ag‐Y alloys for use as resorbable bone fixation implant

Abstract: Magnesium (Mg) alloy is gaining more interest because of its degradability and osteogenic potential. Still, it has some deficiencies, such as its rapid degradation rate, insufficient mechanical property. This research aimed to design a novel biodegradable Mg-argentum (Ag)-yttrium (Y) alloy, and Y was added to improve degradable and mechanical property. Mg-Ag-Y alloys were characterized for mechanical features, practicabilities in vitro and in vivo. The mechanical features results shown that this novel componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 46 publications
0
41
0
Order By: Relevance
“…11 The alkalinity induced by abundant hydroxides and hydrogen might also damage the surrounding tissue. 20 However, no obvious inflammation or systemic adverse reaction was observed in this study.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…11 The alkalinity induced by abundant hydroxides and hydrogen might also damage the surrounding tissue. 20 However, no obvious inflammation or systemic adverse reaction was observed in this study.…”
Section: Discussionmentioning
confidence: 50%
“…Magnesium matrix materials have been widely studied in many medical fields. 7,1518 Mg implants have been made to evaluate the treatment of patients using Mg medical devices in bone and ligament healing, 1921 gastrointestinal anastomosis, 22 biliary tract anastomosis, 16 cardiovascular stents, 17,18 laryngeal applications, 23 compressed sciatic nerves repair, 24 and so on. For example, in bone surgery, Han et al proved that a high-purity Mg screw showed good osseointegration and increased bone mineral density and thus has great potential for internal fixation devices in intra-articular fracture operations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of REE as alloying elements is controversial from a medical point of view but elements such as Y, Nd, Gd can improve the strength, ductility and corrosion resistance of the material. Yu et al (2018) assessed the in vivo corrosion behaviour and osteogenic potential of a novel Mg-Ag-Y alloy and observed that the corrosion rate of the alloying system was significantly lower and more bone tissue was formed around the implant in comparison to pure Mg, mostly due to the presence of the Y element. Also, using Y as an alloying element, Chou et al (2019) evaluated the in vivo performance of a Mg-Y-Zn-Zr-Ca alloy and reported positive results regarding its biocompatibility but poor corrosion resistance due to the surrounding blood vessels and stress related corrosion that appeared at the osteotomy site of high mechanical loading.…”
Section: Mg-alloysmentioning
confidence: 99%
“…Regarding magnesium alloys containing Ag, their antibacterial effect has been reported for a wide range of the microbial spectrum [22]. However, problems of high corrosion rates [16] and cytotoxicity [23] have also been found, although the cytotoxicity can be decreased while maintaining the antimicrobial effect if a secondary element, such as calcium, is included in the alloy [19].…”
Section: Introductionmentioning
confidence: 99%